Implementasi Evidance Based Nursing Pada Pasien Gout Rematik: Studi Kasus - Nabila, Witri Setiawati; Putri, Lydia Mardison (REAL in Nursing Journal, 2020)
ABSTRACTBackground: Health problems that are often found and spread throughout the world, one of which is Gout Arthritis or what we know as Gout. When uric acid levels get higher and pass normal levels, the uric acid will gradually settle and crystallize. Sedimentation This causes the joint to become inflamed which is marked by signs and symptoms such as pain, swelling, and redness in the joints. Methods: In the implementation, complementary therapy was applied to gouty arthritis patients, namely warm ginger compresses and bay leaf water decoction.. Results: Significant results on the pain scale and changes in uric acid levels were before the intervention scale of pain 8 with uric acid levels of 8.7 mg / dl and after the intervention scale of pain 2 with uric acid levels of 7.8 mg / dl. Concluion: The application of complementary therapy of warm ginger compresses and bay leaf decoction which was done showed improvement in patients suffering from gout. Therefore, the application of evidence-based nursing can be recommended in providing nursing care.Keywords       : Complementary, Family, Gout Athritis